2021
DOI: 10.3390/molecules26030755
|View full text |Cite
|
Sign up to set email alerts
|

Jean-Louis Luche and the Interpretation of Sonochemical Reaction Mechanisms

Abstract: Sonochemistry can be broadly defined as the science of chemical and physical transformations produced under the influence of sound. The use of sound energy is rather a young branch of chemistry and does not have the clear definitive rules of other, more established, divisions such as those in cycloaddition reactions or photochemistry. Nevertheless, there are a few guidelines which can help to predict what is going to happen when a reaction mixture is submitted to ultrasonic irradiation. Jean-Louis Luche, formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The notion that a sonochemical-based reaction is merely a mechanistic rather than a chemical operation was also discussed by Kegelaers et al [77] who, after repeating the same series of experiments as described by Ando et al [75], came to the different conclusion that sonochemical reaction served as a mechanistic approach akin to those from extensive stirring that shortens the reaction time [78] but by itself did not induce a chemical change. Despite various examples of 'true' [79][80][81] and 'false' [82,83] sonochemical reactions in literature, which so far remain as the most common explanations, it is necessary to acknowledge that the exact mechanism of sonication chemistry has not yet been clearly elucidated [84].…”
Section: Discussionmentioning
confidence: 99%
“…The notion that a sonochemical-based reaction is merely a mechanistic rather than a chemical operation was also discussed by Kegelaers et al [77] who, after repeating the same series of experiments as described by Ando et al [75], came to the different conclusion that sonochemical reaction served as a mechanistic approach akin to those from extensive stirring that shortens the reaction time [78] but by itself did not induce a chemical change. Despite various examples of 'true' [79][80][81] and 'false' [82,83] sonochemical reactions in literature, which so far remain as the most common explanations, it is necessary to acknowledge that the exact mechanism of sonication chemistry has not yet been clearly elucidated [84].…”
Section: Discussionmentioning
confidence: 99%
“…At this point, the extremes of temperature and pressure provide an unusual environment or high energy microreactors that allow molecular fragmentation of the gases trapped in the collapsing cavities [14] . However, some chemical transformations have been observed that cannot be explained by the effect of cavitation [65] , [66] ; in these cases, the need for a broader investigation of the aspects that make possible the occurrence of chemical reactions by irradiation of ultrasonic waves is implicit .…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980′s, the Luche group began the investigations into the effects of ultrasound on chemical reactions and the mechanistic pathways involved in sonochemistry [66] . In this regard, in a seminal paper published in 1996, Luche and col. categorize sonochemical reactions into three groups [66] : homogeneous sonochemistry: reactions that fall into this category are governed by a radical route, in which the intermediates (radicals or radical ions) are generated by cavitation in homogeneous media. In this case, sonication would be able to promote reactions by means of radicals and ionic reactions could not be modified by such irradiation; this would be the “real” sonochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…However, ultrasonic activation invariably results in an increased temperature of the irrigant in the root canal [ 21 ] and may also be hampered by the altered physical features of a combined NaOCl & HEDP solution [ 14 , 17 ]. Moreover, the so-called “sonochemical” effects of NaOCl, i.e., the expediting of chemical reactions in aqueous solution by ultrasound, albeit somewhat enigmatic [ 22 , 23 ], may be linked to increased local temperature in cavitation bubbles [ 24 ]. This may accelerate the chemical interaction between NaOCl and HEDP even more, thus leading to a quicker loss in available chlorine [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%